Comprehensive analyses unveil novel genomic and immunological characteristics of micropapillary pattern in lung adenocarcinoma - Huo, Yansong; Sun, Leina; Yuan, Jie; Zhang, Hua; Zhang, Zhenfa; Zhang, Lianmin; Huang, Wuhao; Sun, Xiaoyan; Tang, Zhe; Feng, Yingnan; Mo, Huilan; Yang, Zuoquan; et al. (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) usually contain heterogeneous histological subtypes, among which the micropapillary (MIP) subtype was associated with poor prognosis while the lepidic (LEP) subtype possessed the most favorable outcome. However, the genomic features of MIP subtype responsible for its malignant behaviors is substantially unknown. In this study, 8 FFPE samples from LUAD patients were micro-dissected to isolate MIP and LEP components, then sequenced by whole-exome sequencing. More comprehensive analyses involving our samples and public validation cohorts on the two subtypes were performed to better decipher the key biological and evolutionary mechanisms. As expected, the LEP and MIP subtypes exhibited largest disease free survival (DFS) difference in our patients. EGFR was found with highest mutation frequency. Additionally, shared mutations were observed between paired LEP and MIP components from single patients and recurrent mutations were verified in Lung-Broad, Lung-OncoSG as well as TCGA-LUAD cohort. Distinct biological processes or pathways were involved in the evolutionary of the two components. Besides, analyses on copy number variation (CNV) and intratumor heterogeneity (ITH) further discovered the possible immunosurveillance escape, the discrepancy between mutation and CNV level ITH and the pervasive DNA Damage Response as well as WNT pathway gene alternations in MIP component. Phylogenetic analysis on 5 pairs of LEP and MIP components further confirmed the presence of ancestral EGFR mutations. Through comprehensive analyses combining our samples and public cohorts, PTP4A3, NAPRT and RECQL4 were identified to be co-amplified. Multi-omics data also demonstrated the immunosuppression prevalence in MIP component. Our results uncovered the evolutionary pattern of the concomitant LEP and MIP components from the same patient that they were derived from same initiation cells and the pathway-specific mutations acquired after EGFR clonal mutation could shape the subtype-specificity. We also confirmed the immunosuppression prevalence in MIP subtype by multi-omics data analyses, which may result in its unfavorable prognosis.